Economic Overview of 2024: Trends and Challenges - Gubad Ibadoghlu (Turan, 2025)
In this paper, an analysis of Azerbaijan's economic and social performance in 2024 is presented, highlighting key trends and challenges. The discussion covers macroeconomic indicators, sectoral contributions, investment dynamics, regional disparities, and issues related to transparency and data credibility. By examining these aspects, the paper provides a comprehensive overview of the country's economic landscape, identifying emerging opportunities and persistent obstacles to sustainable development.
Keywords: 330; Azerbaijan; macroeconomic indicators; 2024; GDP growth; sectoral contributions; investments; employment; regional economic disparities; Inflation; unemployment; poverty